Performing Wellness: Playing in the Spaces Between Music Therapy and Music Performance Improvisation Practices - Seabrook, Deborah (Voices: A World Forum for Music Therapy, 2017)
This is the accompanying paper to an arts-based pilot project that musically explored interdisciplinarity between improvisation in music therapy and music performance. A culminating concert that brought elements of music therapy improvisation to the stage (available for viewing online) is where the vital learning from this project resides. This written piece additionally articulates philosophical, theoretical and practical concepts and questions that arose from the investigation. Elements of music therapy and music performance improvisation are compared, contrasted, and combined from within the author’s experience. The emergent potential of improvised musical performances for health and wellbeing is also discussed.